CONTRAST EFFECT AND DISPUTE RESOLUTION – AN EXPERIMENTAL STUDY - Mojašević, Aleksandar; Radulovic, Branko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The subject of this paper is the contrast effect in negotiations from the behavioral economics perspective. We conducted an experimental study using a “divorce litigation game” with complete information about payoffs aimed at testing whether participants are prone to context-dependent decisions. The sample was created by 100 law students from the Faculty of Law of the University of Niš. In a “between subjects” design 100 different participants were tested in the control and treatment group. The main finding is that there is a statistically significant difference between the two groups, thus confirming the presence of the contrast effect. The study opens the door to further real experiments with an emphasis on other subjects, such as lawyers, checking if they are so “rational”.